2016
DOI: 10.4049/jimmunol.1501481
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Major Vault Protein Plays a Pivotal Role in Double-Stranded RNA– or Virus-Induced Proinflammatory Response

Abstract: Pathogen invasion triggers robust antiviral cytokine production via different transcription factor signaling pathways. We have previously demonstrated that major vault protein (MVP) induces type I IFN production during viral infection; however, little is known about the role of MVP in proinflammatory responses. In this study, we found in vitro that expression of MVP, IL-6, and IL-8 was inducible upon dsRNA stimulation or viral infection. Moreover, MVP was essential for the induction of IL-6 and IL-8, as impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…Last, MVP is the major subunit of the vault complex, a multiprotein structure involved in nucleocytoplasmic transport. It is induced by double-stranded RNA and virus infection and is essential for the induction of interleukin-6 (IL-6) and IL-8, suggesting an important role in host proinflammatory response (59). High expression of MVP has been shown to suppress viral replication by inducing a type 1 interferon response through nuclear factor κB, establishing a further link with the inflammatory component identified in the module analysis (60).…”
Section: Discussionmentioning
confidence: 99%
“…Last, MVP is the major subunit of the vault complex, a multiprotein structure involved in nucleocytoplasmic transport. It is induced by double-stranded RNA and virus infection and is essential for the induction of interleukin-6 (IL-6) and IL-8, suggesting an important role in host proinflammatory response (59). High expression of MVP has been shown to suppress viral replication by inducing a type 1 interferon response through nuclear factor κB, establishing a further link with the inflammatory component identified in the module analysis (60).…”
Section: Discussionmentioning
confidence: 99%
“…MVP is involved in the diversely cellular processes, including multiresistant cancers, signal transmission pathways, and immune response associated with viral infection and treatment . Viruses with divergent virulence and spreadways can cause diverse human diseases with different types and degrees of damage, as a response of viral infection, studies have confirmed that MVP is enhanced in diverse viral infection, including HBV, HCV, HIV, IAV and VSV, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The interferon regulatory factor 7 (IRF7) plays the master transcriptional role in viral infection‐induced IFN production and immune responses, activates IFN‐β production mediated by MyD88 (myeloid differentiation primary response 88)‐independent RIG‐1/MDA5 pathway, also activates IFN‐α production mediated by the MyD88‐dependent TLRs pathway . The IFN‐1 inhibits viral replication (including HCV, influenza A virus [IAV], and HIV) by the production of IFN‐stimulated effective proteins …”
Section: Mvp Plays Inhibition Function In Viral Replication By Inducimentioning
confidence: 99%
See 2 more Smart Citations